Multiply (x + 6)(x - 8)

(x + 6)(x - 8)
= x^2 - 8x + 6x - 48
=x^2 - 2x - 48

Question

Asked 1/2/2013 8:19:08 PM

Updated 10/12/2014 9:41:05 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [10/12/2014 9:41:03 AM], Confirmed by andrewpallarca [10/12/2014 9:41:05 AM]

s

Rating

There are no new answers.

2x + 6+ 5x -3 = **Weegy:** Answer = 63. (More)

Question

Updated 1/2/2013 8:05:53 PM

1 Answer/Comment

2x + 6+ 5x -3 = 7x + 3

Added 1/2/2013 8:05:55 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [10/12/2014 9:42:05 AM]

(x+1)(x^2+5x-2) **Weegy:** Multiply each term in the first polynomial the second polynomial and then use the distributive property.
x(x^2 + 5x + 2) - 1(x^2 + 5x + 2)
x^3 + 5x^2 + 2x - x^2 - 5x - 2
x^3 + 4x^2 - 3x - 2 [ ] (More)

Question

Expert Answered

Updated 10/12/2014 9:45:49 AM

1 Answer/Comment

(x + 1)(x^2 + 5x 2)

= x^3 + 5x^2 + x^2 - 2x + 5x - 2

=x^3 + 6x^2 + 3x - 2

= x^3 + 5x^2 + x^2 - 2x + 5x - 2

=x^3 + 6x^2 + 3x - 2

Added 10/12/2014 9:45:49 AM

This answer has been confirmed as correct and helpful.

3(x +13) **Weegy:** -2 (More)

Question

Updated 1/2/2013 8:06:27 PM

1 Answer/Comment

3(x +13) = 3x + 39

Added 1/2/2013 8:06:27 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [10/12/2014 9:41:38 AM]

(x+6)(x-8) **Weegy:** Please clarify your question.Thank you. (More)

Question

Expert Answered

Updated 10/12/2014 9:42:27 AM

1 Answer/Comment

(x + 6)(x - 8)

= x^2 - 8x + 6x - 48

=x^2 - 2x - 48

= x^2 - 8x + 6x - 48

=x^2 - 2x - 48

Added 10/12/2014 9:42:24 AM

This answer has been confirmed as correct and helpful.

34,827,777

questions answered

There are no comments.